A targeted population carrier screening program for severe and frequent genetic diseases in Israel - Zlotogora, Joël (Nature Publishing Group, 2009)
A national carrier screening program targeted at communities in which severe genetic diseases are present with a frequency higher than 1/1000 live births, has been in existence in Israel since 2002. Within the communities at risk, carrier screening is voluntary whereas genetic counseling and testing is provided free of charge. During the first 5 years of the program more than 13 000 tests were performed, and at the end of 2007 it was offered in 35 different localities/communities for a total of 36 diseases. Many of the couples identified to be at risk opted for prenatal diagnosis and in two cases an affected pregnancy was terminated. In some cases the couples declined prenatal diagnosis and two of those families gave birth to an affected child. Based on the experience learnt from this targeted screening program it appears that a knowledge-based, voluntary screening program operated within the community is an effective way to provide genetic services and test referrals. The community program directed toward couples in their reproductive period does not seem to have led to stigmatization at either the individual or the community level.